2020
DOI: 10.1073/pnas.2004289117
|View full text |Cite
|
Sign up to set email alerts
|

Most invasive species largely conserve their climatic niche

Abstract: The ecological niche is a key concept for elucidating patterns of species distributions and developing strategies for conserving biodiversity. However, recent times are seeing a widespread debate whether species niches are conserved across space and time (niche conservatism hypothesis). Biological invasions represent a unique opportunity to test this hypothesis in a short time frame at the global scale. We synthesized empirical findings for 434 invasive species from 86 studies to assess whether invasive specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
249
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(270 citation statements)
references
References 48 publications
14
249
6
1
Order By: Relevance
“…S3), are consistent with the study modeling climatic niches. These results are consistent with a recent meta-analysis showing niche conservatism between the native and introduced ranges of many invasive species (Liu, Wolter, Xian, & Jeschke, 2020). Although the climatic niche in the introduced range is not currently as wide as that of the native range, invasive M. guttatus populations seem poised to occupy a greater climatic niche space should it become available.…”
Section: Discussionsupporting
confidence: 92%
“…S3), are consistent with the study modeling climatic niches. These results are consistent with a recent meta-analysis showing niche conservatism between the native and introduced ranges of many invasive species (Liu, Wolter, Xian, & Jeschke, 2020). Although the climatic niche in the introduced range is not currently as wide as that of the native range, invasive M. guttatus populations seem poised to occupy a greater climatic niche space should it become available.…”
Section: Discussionsupporting
confidence: 92%
“…It has been frequently shown that invasive species may evolve new climatic tolerance ranges in their invasive ranges by comparison to their native ranges, although this is not universally true, and in fact a recent analysis of 86 studies examining 434 invasive species concluded the invasive niches are largely conserved (Liu et al, 2020b). Still, the exceptional cases are critical species to monitor.…”
Section: Evidence Of Rapid Evolution On Invasion Edgesmentioning
confidence: 99%
“…Yet, established invasive species are thought to conserve their niche in general, although studies assessing these climatic niche shifts have predominantly focused on plants (Guisan et al., 2014; Liu et al., 2020a; Petitpierre et al., 2012). Terrestrial ectotherms may have a higher capacity for colonization of new climates compared to endotherms (Liu et al., 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, established invasive species are thought to conserve their niche in general, although studies assessing these climatic niche shifts have predominantly focused on plants (Guisan et al., 2014; Liu et al., 2020a; Petitpierre et al., 2012). Terrestrial ectotherms may have a higher capacity for colonization of new climates compared to endotherms (Liu et al., 2020a). Additionally, climatic niche shifts have been considered common in invasive insects (Bates et al., 2020; Hill et al., 2017), but studies report niche conservatism in key invasive insect species (Cunze et al., 2018; Roura‐Pascual et al., 2006).…”
Section: Introductionmentioning
confidence: 99%